2017
DOI: 10.21608/ejar.2017.148763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Fertilization for Olive Trees on the Bioactive Compounds, Purity and Organoleptic Attributes of Olive Oils

Abstract: his investigation was carried out during two seasons 2014 and 2015 at farm located EL-Nobarya, EL-Behera governorate, Egypt, to study the influence of foliar fertilization with soluation of potassium and magnesium sulphate at ratios of 3 and 5% and 0.5 and 1.5%, respectively, on the organolyptic attributes, purity, overall quality index, stability, bioactive compounds (tocopherols, pigments, polyphenols and diortho phenols) and phenolic compounds of Koronaki olive oil under the environmental condition. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In addition to genotype, different chemical environments can cause differences in the enzymatic activity. The levels of available nutrients and their translocation in the plant can significantly affect olive oil quality, so the application of foliar fertilizers can be used to optimize the chemical composition of olive oil and enrich it with beneficial phytochemicals [12]. Nitrogen (N) is a widely used fertilizer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to genotype, different chemical environments can cause differences in the enzymatic activity. The levels of available nutrients and their translocation in the plant can significantly affect olive oil quality, so the application of foliar fertilizers can be used to optimize the chemical composition of olive oil and enrich it with beneficial phytochemicals [12]. Nitrogen (N) is a widely used fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Both resulted in a higher concentration of volatile compounds in general. Atta et al [12] reported that foliar application of magnesium (Mg) and K sulfate resulted in higher intensity of olive fruity attribute, but also positively affecting other desirable sensory attributes. Regni et al [28] found that N foliar fertilization did not cause any change in the sensory attributes of oil.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium deficiencies can be overcome with MgSO 4 0.5-3%, while MgO solutions were found to ameliorate the yield and oil quality (Gavalas, 1978;Zouari et al 2014;Tekaya et al 2016;Atta, Mohamed 2017). The results also indicated that foliar application with MgSO 4 , especially at 1.5%, improved the vegetative growth, fruit set, yield, fruit and oil quality of 'Koroneiki' olives (Mahmoud et al 2017).…”
mentioning
confidence: 97%
“…Moreover, the K spray application frequency affects the Fe and Zn concentrations in olive stems and leaves (Saykhul et al 2014). A positive effect was observed with foliar KNO 3 applications on the salinity tolerance (Larbi et al 2019) and, furthermore, the K 2 SO 4 application improved the freezing tolerance and oil quality (Petridis et al 2012;Atta, Mohamed 2017;Saadati et al 2020).…”
mentioning
confidence: 98%